Cholesterol biosynthesis as a drug-induced vulnerability in diffuse large B cell lymphoma insensitive to EZH2 inhibition - Niccolai, Rachele; Göbel, Camiel; Ndoj, Klevis; Kreft, Maaike; Kuiken, Hendrik J.; Lieftink, Cor; Morris, Ben; Yska, Sietse D.; Hendrix, Sebastian; van den Broek, Bram; Pappalardo, Vincent; Kersten, Marie José; et al. (Neoplasia (New York, N.Y.), 2025)
•GCB-DLBCL insensitive to EZH2 inhibition become dependent on cholesterol synthesis.•This dependency relates to altered LDLR subcellular localization and LDL uptake.•EZH2 inhibition attenuates activation of SREBP2 targets. The methyltransferase EZH2 is a critical epigenetic writer in Germinal Center B cell-like Diffuse Large B Cell Lymphoma (GCB-DLBCL). Clinically and experimentally, GCB-DLBCLs are either sensitive or insensitive to EZH2 inhibition. We hypothesized that EZH2 inhibitor (EZH2i) exposure of the insensitive subset may unfold epi‑drug induced, therapeutically exploitable dependencies. An EZH2i-anchored CRISPR-Cas9 drop-out screen identified the cholesterol biosynthesis pathway as an essential co-target in sensitizing EZH2i-insensitive GCB-DLBCLs. Mechanistic investigations into this metabolic dependency revealed that the loss of EZH2 activity impairs the exogenous cholesterol uptake due to reduced surface expression of the low-density lipoprotein (LDL) receptor, which accumulated in the lysosomal compartment. The reduced LDL uptake failed to upregulate SREBP2-mediated cholesterol biosynthesis as a compensatory response, rendering cells sensitive to cholesterol biosynthesis inhibition. In support of this, inhibition of EZH2 of cholesterol biosynthesis-deficient GCB-DLBCL xenograft increased tumor survival. Together, our findings identified the cholesterol biosynthesis pathway as a targetable vulnerability specific to EZH2i-insensitive GCB-DLBCL. These data support future translational studies to determine how clinically approved cholesterol inhibitors can be used to improve treatment outcomes for DLBCL patients non-responsive to EZH2 inhibition.